Iron for Florida Turfgrasses - Travis W. Shaddox; J. Bryan Unruh (EDIS)
Iron (Fe) is commonly applied to enhance turfgrass color. Understanding the dynamics of Fe both in the plant and in the soil could greatly enhance your nutrient management programs. The objective of this 4-page publication is to explain the function of Fe within the plant, describe the Fe sources available for turfgrasses, and identify which forms of Fe are most effective in improving turfgrass quality. Written by Travis Shaddox and J.B. Unruh and published by the UF/IFAS Department of Environmental Horticulture, January 2018. http://edis.ifas.ufl.edu/ep551